Hybrid core-shell nanoparticles: photoinduced electron-transfer for charge separation and solar cell application - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Chemistry of Materials, 2009)
We report growth and formation of hybrid core−shell nanoparticle systems, where photoinduced electron-transfer takes place from the II−VI semiconducting core to an organic shell. With the hybrid core−shell nanoparticles, we fabricate devices so that the photoinduced electron-transfer can finally yield photocurrent and result photovoltaic solar cells. Formation of an organic shell-layer on CdSe nanoparticles is supported by electronic absorption spectroscopy. Electron-transfer from the nanoparticle in the core to a number of organic molecules in the shell is established from quenching of photoluminescence intensity of CdSe nanoparticles as well as from a change in the lifetime of photoluminescence emission. Devices based on the hybrid core−shell nanoparticles in a suitable hole-transporting layer with two dissimilar metal electrodes show efficient photovoltaic performance. Here, following the electron-transfer, electrons flow through the organic molecules and holes, left in the nanoparticles, move through the hole-transporting polymer to the opposite electrodes to yield photovoltaic short-circuit current. The role of CdSe nanoparticles in light-harvesting and charge-generation has been substantiated by control experiments with ZnS nanoparticles in the core. In ZnS-based hybrid core−shell systems, photovoltaic performance is low since photoinduced electron-transfer does not occur from ZnS to the dye.

Near-IR activity of hybrid solar cells: enhancement of efficiency by dissociating excitons generated in PbS nanoparticles - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Applied Physics Letters, 2010)
Photovoltaic devices based on PbSnanoparticles remained inactive in the near-IR region due to a not-so-favorable energy band-diagram that does not allow dissociation of excitons generated in PbS. In this work, with the introduction of nanostructures in the PbS-based hybrid system, we show an enhancement of photovoltaic performance in both visible and near-IR regions. The addition of increases the power conversion efficiency from 0.006% to 0.12%. With the aid of energy band-diagram, we show that excitons generated in PbS even in the near-IR range can now become dissociated to yield photocurrent in the external circuit.

To make polymer: quantum dot hybrid solar cells NIR-active by increasing diameter of PbS nanoparticles - Guchhait, Asim; Rath, Arup Kumar; Pal, Amlan J. (Solar Energy Materials and Solar Cells, 2011)
We fabricate NIR-active solar cells based on PbS quantum dots and a conventional conjugated polymer. These devices act as solar cells under exclusively NIR wavelengths above 650 nm. Here PbS nanoparticles absorb photons in the NIR range that in turn generate excitons. We show that with an assistance from a strong electron-acceptor (TiO2), these excitons can be dissociated to electrons and holes to yield a photocurrent in the external circuit. We then aim to extend the spectral window of the solar cells to higher wavelength region by increasing the diameter of PbS nanoparticles to make the cells further NIR-active. We observe that the short-circuit current (JSC) shows a peak when the diameter of PbS nanoparticles increases. Here, the spectral window can be extended till conduction band-edge of PbS quantum dots falls below that of TiO2 nanostructures cutting off the electron-transfer pathway. The NIR-active photovoltaic solar cells yield a short-circuit current (JSC) of 1.0 mA/cm2, open-circuit voltage (VOC) of 0.42 V, and power conversion efficiency (η) of 0.16% and remain operative till 1200 nm.